The Higher Education Sector and the Trend towards the Entrepreneurial University - With Reference to Algeria - - بن شواط , سمية; قادري , رياض (Finance and Business Economies Review, 2021)
The research paper aims to present the three European higher education models: the Humboltian, Napoleon, and Anglo-Saxon model in addition to the Anglo-American model, while presenting the third mission of the university with an explanation of the transition from mode 1 to mode 2 and mode 3 in the production of knowledge and the trend towards entrepreneurial universities with triple helix and the academic model of entrepreneurship, then presenting a summary of the efforts of the higher education sector in Algeria currently in response to the changes taking place in the light of the knowledge society. The study found that the higher education sector in Algeria is trying to adapt to the environmental changes taking place as a result of the developments that have imposed on universities contributing to the knowledge society by creating relationships with various government and industry agencies to support graduates and instill a spirit of creativity and innovation and push them to participate in social and economic development through the various facilities that It is established by the university in the framework of cooperative relations.